PEGARUH KOMPLEKSITAS OPERASI PERUSAHAAN, RAPAT KOMITE AUDIT DAN KEPEMILIKAN OPERASIONAL TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2016 – 2018) - Aisyah Aisyah; Andreas Andreas; Natariasari Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study is to obtain empirical evidence about the influence of the complexity of the operations of the company. The type of data used in this study is secondary data. The population includes all mining companies listed on the Indonesia Stock Exchange from 2016 to 2018 that publish financial reports that show data that supports the analysis of the factors that affect the audit report lag. The number of samples in this study were 27 companies with a purposive sampling method. Further data analysis used multiple regression analysis and hypothesis testing with a significant level α = 0.05 with the help of the SPSS application program version 25.0. The results showed that the complexity of the company's operations had a significant effect on the audit report lag with a significant value of 0.002. Audit comet meetings have a significant effect on the audit report lag with a significant value of 0.014. Meanwhile, institutional ownership does not have an effect on the audit report lag because the significant value is 0.129.Keyword: Audit report lag, complexity of company operations, committee meetings, institutional ownership